Affordable Care Act: A review and discussion of its impact on healthcare today, and a primer for pharmacists - Leo Lai Ho Lui; Albert Wertheimer (University of Minnesota Libraries Publishing, 2013)
In the midst of countless healthcare debates, the Patient Protection and Affordable Care Act is written into legislation as a possible solution to the United States's rising healthcare costs. Individualized into nine titles, the act sought to provide additional coverage to millions of Americans while cutting down healthcare costs through numerous provisions effective into 2020. While the act has been challenged publicly and privately by the states, many healthcare professionals today, let alone the average American, are unaware and uneducated of what comprises the act, as well as the impact in which it has on the future of healthcare in the United States. With an increasing role of patient care placed upon pharmacists today, an understanding of the PPACA allows us to provide extensive answers to questions in which our patients may have.   Type: Student Project